Training & Rehabilitation - Pakzad-Mayer Y; Chan Y-S; Jang J-T; Mayer PK (Dynamic Media Sales Verlag, 2019)
Balance plays an important role in the daily lives of elderly people to prevent them from falls and injuries. A suitable exercise to improve balance is Tai Chi Chuan. The purpose of this study was to analyze balance control in Tai Chi Chuan practitioners and compare it with non-practisingactive elderly people.Ten Tai Chi Chuan practitioners, mean age 70.14, (5 womenand 5 men) were willing to participate in this study. Twelve elderly with amean age of 71.95 years, served as the control group. An oscillating suspended platform (Posturomed) was used to measure the horizontal movements in two orthogonal directions using a small ultrasonic marker (Microswing). The measured displacements in the two directions, anterior-posterior (AP) and medio-lateral (ML), were used to establish a balance index. The total sway line g can be divided into the x- and y-component (ML and AP sway). Four different stances were analyzed to evaluate balance ability: shoulder-wide stance with eyes open and closed, legs together, semitandem and tandem stance. An independent t-test was used to compare the groups. The Tai Chi Chuan group showed a significantly (p=0.04) better balance control in the ML direction in the shoulder-wide stance with eyes closed than the control group. In summary, practicing Tai Chi Chuan may have a positive influence on balance control when vision is obstructed and balance has to rely on the vestibular system. KEY WORDS: Postural Sway, Proprioception, Aging, Exercise